Territorialização do capital e as contradições da educação do campo na microrregião de Três Lagoas (MS) - Lemes, Mariana Santos (2014)
This work starts from the perspective of understanding the process of incorporating paradigms that constitute the concept of Rural Education and Rural Education , specifically in three rural schools in the microregion of Três Lagoas , eastern Mato Grosso do Sul nicer essentially identifying which of these paradigms with respect to the practices that permeate the process of territorialization of ongoing capital in Três Lagoas , since the forestry sector ( pulp and paper ) puts in motion a educational - environmental project identified with Education rural representative of agrarian capitalism modernization of the countryside in contrast to the field Education ( educational policies that address the specifics of the field ) project. Thus we see that the Draft Environmental Education -PEA developed by this company applies the ideological discourse of capital through the practice of social responsibility while using education as the easing of conflicts and legitimacy of environmental assessments arising from monoculture eucalyptus. However other project initiatives compatible with the Field Education are found as optimizing a possible change in the educational field.